Reporting, recording, and communication of COVID-19 cases in workplace: data protection as a moving target. Issue 1 (22nd April 2020) - Shabani, Mahsa; Goffin, Tom; Mertes, Heidi
Abstract: In response to concerns related to privacy in the context of coronavirus disease 2019 (COVID-19), recently European and national Data Protection Authorities (DPAs) issued guidelines and recommendations addressing a variety of issues related to the processing of personal data for preventive purposes. One of the recurring questions in these guidelines is related to the rights and responsibilities of employers and employees in reporting, recording, and communicating COVID-19 cases in workplace. National DPAs in some cases adopted different approaches regarding duties in reporting and communicating the COVID-19 cases; however, they unanimously stressed the importance of adopting privacy-preserving approaches to avoid raising concerns about surveillance and stigmatization. We stress that in view of the increasing use of new data collection and sharing tools such as 'tracing and warning' apps, the associated privacy-related risks should be evaluated on an ongoing manner. In addition, the intricacies of different settings where such apps may be used should be taken into consideration when assessing the associated risks and benefits.